MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATERI SISTEM GERAK TUMBUHAN MENGGUNAKAN MODEL PEMBELAJARAN INQUIRY KELAS VIII SMP ISLAM MAYANGAN GUMUKMAS JEMBER TP.2016/2017 - Siti Baidatun Munawaroh; Diah Sudiarti; Laila Khusnah (JURNAL BIOSHELL, 2017)
Educations  is very important  to make a good or bad  of  individual innormative. Learn is a work or activites that apose to turn persons, also in turning behavior, attitudes, traditions, knowledges, and skill. This research attempts to increasing the activity of student learning to learn the matter of moving system  in plants on the Inquiry model. Type of research is use classroom actions research (CAR). The procedure use a cycle model, based on the result of research data showed 43,2% of student learning activity on the first cycle and 86% on the second cycle. While in the learning outcomes of students on the first cycle showed 46% and 81% on the second cycle. This case proves that the activity and learning outcomes of students can  increase by Inquiry model, make students think and  be active in the process of intelectual activity and learning experiences is something meaningfull in real life, tested by experimenting to answer questions that real, conclude hypotesis and conclusions.Keywords: Model  Inquiry Learning, Learning Activity